Reactions in micellar systems: Prediction of partition coefficients. - Wille, Susanne; Schwarze, Michael; Mokrushina, Liudmila; Smirnova, Irina; Schomäcker, Reinhard; Arlt, Wolfgang (Abstracts of Papers, 239th ACS National Meeting, San Francisco, CA, United States, March 21-25, 2010, 2010)
Micellar systems offer the advantage to solubilize hydrophobic reactants, products, and catalysts without using org. solvents. In those systems, the ratio of reactant, product or catalyst concns. between the aq. and the micellar phase (so-called partition coeffs.) has a substantial influence on the reaction kinetics. Therefore, optimization of reaction conditions in micellar systems can be done based on the partition coeffs. This information can be used to design tailor-made surfactants. In the present study, the partition coeffs. are obtained by an a priori prediction using COSMO-RS (Conductorlike Screening Model for Real Solvents). This model is based on quantum mechanics and needs only the structure of reactants, products, and catalysts as an input. It is demonstrated that the hydrogenation reaction conditions can be optimized by choosing the most suitable surfactant and catalyst based on the prediction results. We thank German National Science Foundation (grant AR 236/32-1) for financial support. [on SciFinder(R)]